Social media for government : a practical guide to understanding, implementing, and managing social media tools in the public sphere - Khan, Gohar F. (Springer, 2017)
This book provides practical know-how on understanding, implementing, and managing main stream social media tools (e.g., blogs and micro-blogs, social network sites, and content communities) from a public sector perspective. Through social media, government organizations can inform citizens, promote their services, seek public views and feedback, and monitor satisfaction with the services they offer so as to improve their quality. Given the exponential growth of social media in contemporary society, it has become an essential tool for communication, content sharing, and collaboration. This growth and these tools also present an unparalleled opportunity to implement a transparent, open, and collaborative government. However, many government organization, particularly those in the developing world, are still somewhat reluctant to leverage social media, as it requires significant policy and governance changes, as well as specific know-how, skills and resources to plan, implement and manage social media tools. As a result, governments around the world ignore or mishandle the opportunities and threats presented by social media. To help policy makers and governments implement a social media driven government, this book provides guidance in developing an effective social media policy and strategy. It also addresses issues such as those related to security and privacy.
Keywords: Internet in public administration.; Social media.; elektronické knihy; electronic books